Seasonality of nitrous oxide emissions at six full-scale wastewater treatment plants - Milla Sieranen; Helena Hilander; Henri Haimi; Timo Larsson; Anna Kuokkanen; Anna Mikola (Water Science and Technology, 2024)
Nitrous oxide (N2O) is an ozone-depleting greenhouse gas that contributes significantly to the carbon footprint of a wastewater treatment plant (WWTP). Plant-specific measurement campaigns are required to reliably quantify the emission level that has been found to significantly vary between WWTPs. In this study, the N2O emissions were quantified from five full-scale WWTPs during 4–19-day measurement campaigns conducted under both cold period conditions (water temperature below 12 °C) and warm period conditions (water temperature from 12 to 20 °C). The measurement data were studied alongside long-term monitoring data from a sixth WWTP. The calculated emission factors (EFs) varied from near 0 to 1.8% relative to the influent total nitrogen load. The results confirmed a significant seasonality of N2O emissions as well as a notable variation between WWTPs in the emission level, which a single fixed EF cannot represent. Wastewater temperature was one explanatory factor for the emission seasonality. Both low and high emissions were measured from denitrifying–nitrifying activated sludge (AS) processes, while the emissions from only nitrifying AS processes were consistently high. Nitrite (NO2-) at the end of the aerobic zones of the AS process was linked to the variability in N2O emissions during the cold period. HIGHLIGHTS N2O emissions exhibit seasonal variability that can be linked to wastewater temperature.; Fixed emission factors are highly unrepresentative of the variability in N2O emissions between treatment plants.; N2O emissions are higher in only nitrifying processes than in nitrifying–denitrifying processes.; Process disturbances may significantly affect the N2O emission level during short-term monitoring.;